From Trade War to Global Tension: Trump’s Economic Policies and Sustainable Peace - Erekata, Famous Oghenewetha; Chekube, Okswuokei Vivian (International Journal of Public Administration and Policy, 2025)
The Trump administration introduced a notable transformation in the United States' foreign and economic policy, primarily through assertive trade measures that heightened global economic tensions. This study explored the extent to which the administration’s trade confrontations, particularly with China, contributed to growing geopolitical instability and posed challenges to maintaining international peace. It focused on the effects of protectionist economic strategies on global diplomatic relations and examined their broader implications for long-term stability. Utilizing a historical research approach, it draws on a range of primary and secondary materials, such as political speeches, trade documents, policy records, and academic literature. This study adopted the Realist Theory of International Relations as its guiding framework, emphasizing how Trump’s economic policies were driven by national self-interest and the pursuit of power within the global system. The study found that policies such as the imposition of unilateral tariffs, the retreat from multilateral trade agreements, and the use of combative rhetoric weakened alliances, disrupted international trade networks, and heightened diplomatic tensions, particularly with China. These developments undermined global cooperative systems and eroded mechanisms intended to address economic disputes peacefully. The study concluded that although the policies were designed to protect American economic interests, they unintentionally fueled international discord and threatened global peace efforts. It recommends, among others, that the United States should renew its commitment to multilateral trade systems, including active participation in the World Trade Organization (WTO) and reengagement with regional trade agreements such as the Comprehensive and Progressive Agreement for Trans-Pacific Partnership (CPTPP). Such engagement would reinforce the rules-based global trading system, restore trust with international partners, and foster collaborative economic development rooted in shared norms.